2004
DOI: 10.1603/0022-2585-41.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of a Cecropin Transgene in the Human Malaria Vector MosquitoAnopheles gambiae(Diptera: Culicidae): Effects on Susceptibility toPlasmodium

Abstract: Genetically altering the disease vector status of insects using recombinant DNA technologies is being considered as an alternative to eradication efforts. Manipulating the endogenous immune response of mosquitoes such as the temporal and special expression of antimicrobial peptides like cecropin may result in a refractory phenotype. Using transgenic technology a unique pattern of expression of cecropin A (cecA) in Anopheles gambiae was created such that cecA was expressed beginning 24 h after a blood meal in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
124
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 29 publications
6
124
2
5
Order By: Relevance
“…This reaction could be due to the detected low constitutive activation of REL2-F, to pathway activation by Plasmodium, or both. A recent study has shown that ectopic overexpression of CEC1 drastically reduces susceptibility of mosquitoes to Plasmodium (33). Other REL2-regulated proteins that might explain the observed phenotype are Gambicin (GAM1), another AMP with antiparasitic activity in vitro (34), and LRIM1, a key antagonist of ookinete-tooocyst development (13).…”
Section: Discussionmentioning
confidence: 99%
“…This reaction could be due to the detected low constitutive activation of REL2-F, to pathway activation by Plasmodium, or both. A recent study has shown that ectopic overexpression of CEC1 drastically reduces susceptibility of mosquitoes to Plasmodium (33). Other REL2-regulated proteins that might explain the observed phenotype are Gambicin (GAM1), another AMP with antiparasitic activity in vitro (34), and LRIM1, a key antagonist of ookinete-tooocyst development (13).…”
Section: Discussionmentioning
confidence: 99%
“…gambiae remains problemhAT elements, hobo, Hermes, and Herves, provides a unique opportunity to examine the role that element sequences atic with only three successful transformations reported since 1987 (Miller et al 1987;Grossman et al 2001; within a transposable element family play in determining insertion site specificity. Our data show that Herves, Kim et al 2004). Furthermore, the difficult husbandry of An.…”
Section: Phylogenetic Analyses Aimed At Establishing the Placement Ofmentioning
confidence: 61%
“…Moreira et al 2002;Kim et al 2004), a key remaining obstacle to the extension of this technology remobilization properties of Hermes, piggyBac, and Mos1 in somatic and germ-line nuclei were examined in transto the field remains the absence of gene vectors that can efficiently drive genes through mosquito populations.…”
mentioning
confidence: 99%
“…stephensi and Anopheles albimanus, transformation efficiency was much lower in An. gambiae and more technically challenging 22,23 . Since then, several modifications to the protocol have improved the efficiency considerably, as outlined in Lobo et al 24 .…”
Section: Transposon Mediated Germ-line Transformation Of An Gambiaementioning
confidence: 99%